Estudo dos resíduos perigosos do campus de Araras da Universidade Federal de São Carlos visando a sua gestão - Saqueto, Karla Carolina (2010)
For that management of the hazardous wastes be held of correct environmental way, technical and administrative arrangements should be implemented, involving the prevention and effective control of generation until its final disposition. Considering the importance and complexity of the wastes management at universities, the objective of this work is to make a diagnosis and analysis of the questions involving dangerous wastes generated by the Centre for Agrarian Sciences - UFSCar campus from Araras city, in order to propose management of these wastes, with the aim of promoting reduction and/or elimination of the environment impact caused by improper discard, based on necessities and particularities of UFSCar campus and literature related. Were discussed some important concepts about thematic of wastes in the university, as well as the best ways of management of hazardous wastes in theses institutions. Aiming to set particularities of the campus from Araras city was accomplished the diagnose and characterization of the dangerous wastes by applying a semi-structured interview with the manager staff of the wastes sectors. Due the diversity of labs, 116 differents itens of wastes are generated, these wastes can be separated in categories and they present different degree of risk. However, in the campus from Araras city are storaged more than a half (54,4%) of these wastes, considered dangerous, the remainder part of it, is discard of wrong way. The data about waste treatment, show that just 8,5 liters per month of wastes perform some treatment, ie, less than 2% of the total generated. Fortunately, it is feasible that this reality can be changed leading the college to a correct control of their wastes. However it is necessary to create a recycling conscience and informations, that are able to change the complex circunstances present in the university.